Efforts To Improve Learning Outcomes Of Basic Volleyball Underhand Passing Techniques Through Play Method In Class VII.6 Students At SMP Negeri 3 Palembang - Tanzila; Hartati; Siswo Pranoto (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to improve the learning outcomes of the basic underhand passing technique in volleyball through the play method for students of class VII.6 at SMP Negeri 3 Palembang. The method used is Classroom Action Research (CAR), conducted in two learning cycles that include planning, action implementation, observation, and reflection to evaluate and improve the learning process. The research subjects were all 30 students of class VII.6 with a Minimum Completeness Criterion (KKM) of 75. The results showed a significant improvement, with students achieving the KKM score increasing from 12 students (40%) in the pre-cycle, to 19 students (63.3%) in the first cycle, and 26 students (86.7%) in the second cycle. These findings prove that the play method effectively enhances the underhand passing technique while motivating students to learn more actively and enjoyably. Therefore, the play method is recommended as a learning strategy to improve the learning outcomes of the basic underhand passing technique in volleyball at school.